Answer: 47 Step-by-step explanation: Let’s solve your equation step-by-step. −4x−3(−44−23)=13 Step 1: Simplify both sides of the equation. −4x+201=13 Step 2: Subtract 201 from both sides. −4x+201−201=13−201 −4x=−188 Step 3: Divide both sides by -4. −4x −4 = −188 −4 x=47 Log in to Reply

Answer:47Step-by-step explanation:Let’s solve your equation step-by-step.

−4x−3(−44−23)=13

Step 1: Simplify both sides of the equation.

−4x+201=13

Step 2: Subtract 201 from both sides.

−4x+201−201=13−201

−4x=−188

Step 3: Divide both sides by -4.

−4x

−4

=

−188

−4

x=47